Evaluation of CTX-M steady-state mRNA, mRNA half-life and protein production in various STs of Escherichia coli. (26th November 2015) - Geyer, Chelsie N.; Fowler, Randal C.; Johnson, James R.; Johnston, Brian; Weissman, Scott J.; Hawkey, Peter; Hanson, Nancy D.
Abstract: Objectives: High levels of β-lactamase production can impact treatment with a β-lactam/β-lactamase inhibitor combination. Goals of this study were to: (i) compare the mRNA and protein levels of CTX-M-15- and CTX-M-14-producing Escherichia coli from 18 different STs and 10 different phylotypes; (ii) evaluate the mRNA half-lives and establish a role for chromosomal- and/or plasmid-encoded factors; and (iii) evaluate the zones of inhibition for piperacillin/tazobactam and ceftolozane/tazobactam. Methods: Disc diffusion was used to establish zone size. RNA analysis was accomplished using real-time RT–PCR and CTX-M protein levels were evaluated by immunoblotting. Clinical isolates, transformants and transconjugants were used to evaluate mRNA half-lives. Results: mRNA levels of CTX-M-15 were up to 165-fold higher compared with CTX-M-14. CTX-M-15 protein levels were 2–48-fold less than their respective transcript levels, while CTX-M-14 protein production was comparable to the observed transcript levels. Nineteen of 25 E. coli (76%) had extended CTX-M-15 mRNA half-lives of 5–15 min and 16 (100%) CTX-M-14 isolates had mRNA half-lives of <2–3 min. Transformants had mRNA half-lives of <2 min for both CTX-M-type transcripts, while transconjugant mRNA half-lives corresponded to the half-life of the donor. Ceftolozane/tazobactam zone sizes were ≥19 mm, while piperacillin/tazobactam zone sizes were ≥17 mm. Conclusions: CTX-M-15 mRNA and protein production did not correlate. Neither E. coli ST nor phylotype influenced the variability observed for CTX-M-15 mRNA or protein produced. mRNA half-life is controlled by a plasmid-encoded factor and may influence mRNA transcript levels, but not protein levels.